2004
DOI: 10.1189/jlb.0404242
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial endotoxin stimulates macrophages to release HMGB1 partly through CD14- and TNF-dependent mechanisms

Abstract: Bacterial endotoxin [lipopolysaccharide (LPS)] stimulates macrophages to sequentially release early [tumor necrosis factor (TNF)] and late [high mobility group box 1 (HMGB1)] proinflammatory cytokines. The requirement of CD14 and mitogen-activated protein kinases [MAPK; e.g., p38 and extracellular signal-regulated kinase (ERK)1/2] for endotoxin-induced TNF production has been demonstrated previously, but little is known about their involvement in endotoxin-mediated HMGB1 release. Here, we demonstrated that gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
123
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(138 citation statements)
references
References 42 publications
15
123
0
Order By: Relevance
“…Active secretion typically occurs not only in macrophages and monocytes (Chen et al, 2004;Kalinina et al, 2004), but also in nonimmune cells such as hepatocytes where it is overexpressed after hypoxia (Tsung et al, 2005). Here, we suggest that HMGB-1 is released from the ischemic brain parenchyma within 1 h after MCAO, based on early loss of HMGB-1 immunoreactivity in the striatum.…”
Section: Discussionmentioning
confidence: 70%
“…Active secretion typically occurs not only in macrophages and monocytes (Chen et al, 2004;Kalinina et al, 2004), but also in nonimmune cells such as hepatocytes where it is overexpressed after hypoxia (Tsung et al, 2005). Here, we suggest that HMGB-1 is released from the ischemic brain parenchyma within 1 h after MCAO, based on early loss of HMGB-1 immunoreactivity in the striatum.…”
Section: Discussionmentioning
confidence: 70%
“…In addition to this HMGB1 antagonizing effect, we demonstrated in vivo that annexin A5 treatment reduced the serum HMGB1 level in LPS challenged mice ( Figure 4E). The active release of HMGB1 by immune cells is partially dependent on LPS-mediated TLR4 signaling (10,46). We speculate that annexin A5 potentially inhibits the release of HMGB1 by inhibiting both LPSand HMGB1-mediated TLR4 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above findings, it could be speculated that the LPS-induced early inflammatory cytokines may function as intermediating molecules in HMGB1 secretion through enhancing the hyperacetylation and phosphorylation of HMGB1. In contrast, several other reports showed that the inhibition of the early inflammatory cytokines or LPS signaling molecules did not significantly affect HMGB1 release (19,20). Thus, for the complete understanding of the HMGB1 release, the identification of additional molecules that are closely related to the event, but to date elusive, is necessary.…”
mentioning
confidence: 90%